2015 Tenth International Conference on Ecological Vehicles and Renewable Energies (EVER) 2015
DOI: 10.1109/ever.2015.7112996
|View full text |Cite
|
Sign up to set email alerts
|

Optimum magnetic solution for interoperable system for stationary wireless EV charging

Abstract: This paper discusses requirements and potential solutions for interoperable wireless charging systems for electric and plugin hybrid vehicles. Such technology is known as resonant magnetic induction charging, also referred to as wireless electric vehicle charging (WEVC). Future requirements for a WEVC system are: low cost, small package, high power transfer and interoperability.This paper discusses interoperability requirements as a key factor for successful deployment of WEVC systems. One key aspect analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Rectangular coil and DD coil are two widely used coil structures [4], [6]. Previous research reveals that the null points of power and efficiency cannot be eliminated when…”
Section: A Interoperability Of Magnetic Couplersmentioning
confidence: 99%
See 1 more Smart Citation
“…Rectangular coil and DD coil are two widely used coil structures [4], [6]. Previous research reveals that the null points of power and efficiency cannot be eliminated when…”
Section: A Interoperability Of Magnetic Couplersmentioning
confidence: 99%
“…Nowadays, various wireless electric vehicle charging (WEVC) products have been introduced and it is observed that the advantages of WEVC technology include providing automatic charging, increasing device mobility and reducing battery capacity [2]. However, poor interoperability [4], [5] is the bottleneck for WEVC systems. The issues of interoperability can be addressed from the following aspects:…”
Section: Introductionmentioning
confidence: 99%
“…It was found that it is important to use proper simulation domain and region size, specific boundary conditions, a reasonable meshing setup and correct assumptions for material properties and coil currents. For the simulations of the WEVC system considered in this study, the magnetic coils, ferrite layers and shield plates were modelled using the actual material properties of the Litz wire, soft ferrite and aluminium parts provided by data sheets [15][16][17]. The excitations of the BP and VP coil currents used were based on a coil current measurement.…”
Section: Simulationmentioning
confidence: 99%
“…Although the employment of WPT to power LEDs is still uncommon, several papers exploring the effects of resonant coupling on the efficiency of wireless charging of EVs can be found in the literature 10–12 . For example, Tavakoli et al 13 have reported the possibility of using additives in the mortar to increase the power transfer efficiency in the wireless charging process of EVs.…”
Section: Introductionmentioning
confidence: 99%